Espiritualidade na saúde: levantamento de evidências na literatura científica - Vanderlei, Ana Claudia de Queiroz (2010)
This research aimed to review the available evidence in the database of the CAPES´ site about the spirituality/religiosity and health relation, in the decade between 2000 and 2009. It focused on the relationship between the health professionals and the patients as concerns their spiritual lives and during their illnesses of awesome significance nowadays, such as: mental diseases, cardiovascular disease, cancer and AIDS. In this research, 95 studies are described and summarized. Several researches have been developed with the intention to investigate if beliefs, growth in faith and attendance at a community improve health and help people to live longer. It is noteworthy the increasing importance concerning to the relation between spirituality and health inside universities and clinical practice. In most of these studies, religiosity/spirituality has demonstrated a great impact on physical health as a possible factor for preventing the development of diseases and an occasional death reduction or the effect of several illnesses. Experiences, with HIV positive patients or with cancer, point out spiritual health as an important dimension of existence as regards facing the disease. The researches also indicate that religion/spirituality works as protection against cardiovascular diseases due to its inducement for healthy lifestyles, and it is associated with a better physical health predicting, thus, a faster remission of depression. In addition to the patient s spirituality, the caretakers´spiritual matters and how both of them see health and illness as well as how they interact are subjects taken into account. But, although, the theme has been taking part, definitely, in the researches´ list, the empirical studies have presented methodological flaws and limited success in reference to the mechanisms which act by promoting health through the religious involvement. The theme has been considered an intellectual and methodological challenge and it demands more studies before any definitive conclusions about the biological benefit of the spiritual practices come out; especially because such discussion will not end in the near future.